Comparative Bioavailability of Two Different Diclofenac Formulations in Healthy Volunteers - Silva, Lara Cristina; Simões, Inácia Gonçalves; Lerner, Federico Ezequiel; Beleém, Gina Rodrigues; Amaral de Moraesc, Maria Elizabete; De Nucci, Gilberto (Arzneimittelforschung, 1999)
The aim of the study was to assess the bioequivalence of two different diclofenac (CAS 15307-86-5) formulations (diclofenac free acid suspension as test formulation and diclofenac resinate suspension, Cataflam®, as reference formulation) in 24 healthy volunteers. After an overnight fast, the volunteers received a single oral dose (50 mg) of each formulation, following an open, randomized, two-period crossover design, with a fourteen-day washout interval between doses. Serum samples were obtained over a 24-h interval post-dosing, and were analysed for their diclofenac content by HPLC-UV. No adverse effect was reported for any of the formulations administered. Geometric mean test/reference individual ratios were: 92.8 % for AUC(0−24 h), 93.2 % for AUC(0−”), 117.2 % for Cmax, 131.0 % for Ke and 76.2 % for T1⁄2. The variability of Cmax parameter expressed as CV was greater than 25 %. Since the 90 % CI for AUC(0−24 h) mean ratio were within the 80−125 % interval proposed by the Food and Drug Administration, it can be concluded that diclofenac free acid formulation is bioequivalent to diclofenac resinate formulation for the extent of absorption. Since the European Community Agency accepts a 90 % CI for Cmax of 70−143 %, it can be concluded that diclofenac free acid formulation is bioequivalent to diclofenac resinate formulation for both the rate and the extent of absorption after single dose administration.
Keywords: CAS 15307-86-5; Cataflam®; Diclofenac; bioequivalence, pharmacokinetics, volunteers